Optimalisasi Biaya Transportasi Pengiriman Barang dengan Menerapkan Metode Potensial - M Abduh Al Hafidh (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
Costs are expenses that often exist in a company where when expenses are not handled properly it will cause problems in a company. Optimizing costs in the process of sending costs is needed to minimize spending on a company so that expenses will be more focused and will not harm the company. Optimization is a step to reduce expenses on the company. The potential method is one method that is able to overcome the problem of minimizing transportation costs at PT. Bintang Mutiara Cemerlang.Optimization used in companies with potential methods is very effective